Overall mortality in men and women in the randomized Prostate, Lung, Colorectal, and Ovarian Cancer Screening Trial. (September 2019) - Pinsky, Paul F; Miller, Eric A; Zhu, Claire S; Prorok, Philip C
Objective: To assess the secondary outcome of overall mortality in the randomized Prostate, Lung, Colorectal, and Ovarian cancer screening trial. Methods: In the Prostate, Lung, Colorectal, and Ovarian trial, subjects were randomized to usual care or intervention. In the intervention arm, men and women received annual chest radiographs and two sigmoidoscopy exams. Men also received annual prostate-specific antigen tests and digital rectal exams, and women also received annual CA125 tests and trans-vaginal ultrasounds. Poisson regression and Cox proportional hazards models were used to assess differences across trial arms in overall mortality and overall mortality excluding deaths from trial cancers (OMEX ). Due to slight age imbalances in later trial years, age-adjusted rate ratios and hazard ratios were computed. Results: There were 76, 678 men and 78, 209 women randomized, with median follow-up of 17 years. In men there was a significant reduction in both overall mortality (age-adjusted rate ratio = 0.966; 95% CI: 0.943–0.989; p = 0.004) and OMEX (age-adjusted rate ratio = 0.970, 95% CI: 0.946–0.995; p = 0.02) in the intervention versus usual care arm. In women, no reduction was seen in either overall mortality (age-adjusted rate ratio = 1.002) or OMEX (age-adjusted rate ratio = 1.006). In both sexes combined, there was a significant reduction in overall mortality (age-adjusted rate ratio = 0.980; 95% CI: 0.963–0.999; p = 0.036) but not OMEX (age-adjusted rate ratio = 0.985; 95% CI: 0.965–1.004; p = 0.13). Results were similar using age-adjusted hazard ratios. Conclusion: In the Prostate, Lung, Colorectal, and Ovarian trial, there was a small but significant reduction in overall mortality in men, and in both sexes combined, and a small but significant reduction in overall mortality excluding trial cancer deaths in men.